(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Can painting evoke an experience of the sublime, understood in the terms adopted by Kant in the Critique of the Power of Judgment? I will present three considerations that imply that painting cannot evoke the Kantian sublime. I will then point out some problems related to each consideration. I will explain how some paintings can evoke an experience of the sublime, even when painting is understood in terms of the eighteenth-century European context. In this way, I intend to show the real possibility of the Kantian sublime as a reaction to pictorial art.